Triple Synchronous Colorectal Cancer: An Extremely Rare Case Underscoring the Need for Careful Perioperative Evaluation - Phu Van La; Diep Ngoc Nguyen; Dien Minh Tran; Tu Tuan Duong; Minh Thanh Phuoc Tran; Phuc Vinh La; Minh Nhat Thanh Le; Cong Phi Dang; Vu Anh Doan (Gastrointestinal Disorders, 2025)
Synchronous colorectal cancer (SCRC) is characterized by the simultaneous occurrence of two or more primary colorectal malignancies, diagnosed either preoperatively, intraoperatively, or within six months postoperatively. The rare prevalence of SCRC makes it an uncommon scenario among colorectal malignancies. Since the majority of SCRC patients have been reported to have two concurrent malignancies, triple synchronous malignancies are extremely rare. We report the case of a 65-year-old male individual presenting with a history of abdominal pain, anemia, anorexia, and unintentional weight loss. He was diagnosed with synchronous colorectal cancer with three distinct tumors: two located in the splenic flexure and sigmoid colon, respectively, and another in the rectum that caused partial obstruction. This case highlights the importance of intraoperative evaluation and an appropriate choice of surgical intervention in colorectal cancer. The early identification and proper management of multiple colorectal cancers remain essential for better survival rates.